Activin-A, Growth Differentiation Factor-11 and Transforming Growth Factor-β as predictive biomarkers for platinum chemotherapy in advanced non-small cell lung cancer. (2022) - Lim, Jennifer; Murphy, Alexander; Wong, Stephen; Nagrial, Adnan; Karikios, Deme; Daneshvar, Dariush; McCloy, Rachael; Steinmann, Angela M; O'Toole, Sandra; Chin, Venessa
Highlights: The majority of patients with advanced non-small cell lung cancer receiving platinum-based chemotherapy do not receive a clinical benefit. Predictive biomarkers are needed to tailor treatment to patients most likely to receive benefit and limit toxicity exposure. At present, there is no evidence that Activin-A, GDF-11 and TGF-β immunohistochemistry staining are useful predictors of platinum chemotherapy response in the setting of advanced non-small cell lung cancer. Abstract: Background: Despite advances in immunotherapy and targeted therapy, platinum-based chemotherapy remains crucial for many patients with advanced non-small cell lung cancer (NSCLC). Resistance to platinum chemotherapy is common, and predictive biomarkers are needed to tailor treatment to patients likely to respond. In vitro evidence implicates the transforming growth factor-β (TGF-β) superfamily ligands activin-A and growth differentiation factor 11 (GDF-11) in innate platinum resistance. We performed a validation study to assess their utility as predictive biomarkers of platinum chemotherapy response in advanced NSCLC. Patients and Methods: Our study included 123 adult patients with advanced NSCLC without a driver mutation treated with platinum chemotherapy. 98 patients were from a retrospective cohort and 25 from a prospective cohort. We performed immunohistochemistry staining for Activin-A, GDF-11 and TGF-β on tumour samples for each patient and analysed IHC expression with objective radiological response and overall survival. Results: The overall median survival was 14.8 months. We performed statistical analysis around a cytoplasmic score of 8/18 for Activin-A and GDF-11 based on previously published work, and 110/30 for TGF-β based on a calculated cutpoint for significance. No survival difference was detected between these groups for Activin-A (p=0.35), GDF-11 (p=0.57) or TGF-β (p=0.34). There was no association between rates of progressive disease and high Activin-A expression (p=0.43), high GDF-11 expression (p=1.0) or high TGF-β expression p=0.89). Conclusion: Within the confines of our study, Activin-A, GDF-11 and TGF-β expression was not a predictor of objective radiological response to chemotherapy or overall survival.